FLUKTUASI CURAH HUJAN DAN KOMUNITAS SERANGGA DI HUTAN TROPIS TAMAN NASIONAL GUNUNG HALIMUN*[Fluctuation of rainfall and insect community in a tropical forest, Gunung Halimun National Park] - Kahono, Sih; Noerdjito, Woro A (BERITA BIOLOGI, 2001)
Study on fluctuation of rainfall and insect community was conducted in a tropical forest, Gunung Halimun National Park. Ten years rainfall data was available to discuss their fluctuations. Rainfall was relatively non-seasonal with high number of almost entire monthly rainfalls.Although fluctuation of rainfall in GHNP did not show clear seasonal trend, however appearance of less rainfall showed from June to September. There were several slight fluctuations in the number of rainfalls from a month to another and some time showed major and minor peaks. Monthly dry months had never reached 0 mm. In ordinary years, only one-month drought occurred in July 1991 (90 mm) and December 2000 (8 mm). Strong drought occurred only during El Nino of 1994 and 1997, which have 3 to 4 dry months. Fluctuation of insect community was studied from March 2000 up to February 2001. Two insect collection methods were applied by setting up light traps and pitfall traps. Total individual of each order of insect counted monthly and to be compared one to another. Changing the number of monthly individual of each order was interpreted to the number of monthly rainfall in order to analyze the relation of changing of the number of rainfall and the individual of each order of the insect collected. Fluctuation of the number of monthly rainfall was synchronous to the number of insect community collected by light traps (night flying insect) but tend to opposite to the number of insect collected by pitfall traps (ground insect).